Raman scattering study of the (formula presented) system: Rhombohedral-monoclinic-tetragonal phase transitions - Souza Filho, A. G.; Lima, K. C.V.; Ayala, A. P.; Guedes, I.; Freire, P. T.C.; Melo, F. E.A.; Mendes Filho, J.; Araújo, E. B. [UNESP]; Eiras, J. A. (American Physical Society (APS), 2002)
In this paper we present a Raman-scattering study of the phase transitions in the (formula presented) systems around the morphotropic phase boundary over a wide temperature range. The boundary between rhombohedral and monoclinic phases was found to be a quasivertical line between (formula presented) We also studied the monoclinic-tetragonal phase boundary and our spectroscopic results agree very well with those reported by using x-ray diffraction. © 2002 The American Physical Society.